2021
DOI: 10.1155/2021/5565014
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogenic Bacterial and Intestinal Parasitic Infections among Asymptomatic Food Handlers in Rangsit University Canteens, Central Thailand

Abstract: Food handlers play an important role in the transmission of foodborne diseases. 108 asymptomatic food handlers work in RSU canteens and have never been checked for intestinal bacteria and parasites, which might be a potential source of infection for customers. This study is aimed at estimating the prevalence of enteropathogenic bacterial and intestinal parasitic infections among food handlers in Rangsit University canteens, central Thailand. A total of 79 food handlers were enrolled, and each provided one stoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The rate of bacterial fecal carriage was 102 (26.7%), greater than the reports in Gondar (13.2%), 22 Jimma (6.9%), 23 and Thailand (2.5%). 24 Moreover, the prevalence of food The majority of bacteria found in the fecal samples was E. coli (18.5%) which is consistent with a study in Gondar that found E. coli to be prevalent. 25 However, a study reported in Jimma indicated that Salmonella species (40%) was predominant.…”
Section: Associated Factors With Fecal Carriage Bacteria Isolatessupporting
confidence: 88%
See 2 more Smart Citations
“…The rate of bacterial fecal carriage was 102 (26.7%), greater than the reports in Gondar (13.2%), 22 Jimma (6.9%), 23 and Thailand (2.5%). 24 Moreover, the prevalence of food The majority of bacteria found in the fecal samples was E. coli (18.5%) which is consistent with a study in Gondar that found E. coli to be prevalent. 25 However, a study reported in Jimma indicated that Salmonella species (40%) was predominant.…”
Section: Associated Factors With Fecal Carriage Bacteria Isolatessupporting
confidence: 88%
“…Among asymptomatic food handlers, the rate of bacterial carriage in feces and hands were 102 (26.7%), and 214 (55.7%), respectively. The rate of bacterial fecal carriage was 102 (26.7%), greater than the reports in Gondar (13.2%), 22 Jimma (6.9%), 23 and Thailand (2.5%) 24 . Moreover, the prevalence of food‐borne pathogens among food handlers in the prison setting was 72.6% (77/106; from hand swab) and 34.9% (37/106; from fecal samples).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In Thailand, giardiasis has been reported in humans [ 15 , 16 , 17 , 18 ] and in many animals, including dogs [ 19 , 20 ], cats [ 21 ] and long-tailed macaques [ 22 ]. However, information on the prevalence of Giardia infection in captive prairie dogs in Thailand is still limited.…”
Section: Introductionmentioning
confidence: 99%